Coenzyme Q10 supplementation – In ageing and disease. (July 2021) - Aaseth, Jan; Alexander, Jan; Alehagen, Urban
Highlights: Coenzyme Q10 is essential for mitochondrial electron transport and support of proton pump and ATP production. Coenzyme Q10 is an antioxidant protecting membranes and lipoproteins and acts in concert with the selenoenzyme thioredoxin reductase. Ageing and use of statins may result in coenzyme Q10 deficiency and supplementation may alleviate cardiovascular disease and inflammation. Bioavailability of coenzyme Q10 differs according to pharmaceutical formulation. Clinical trials with bioavailable coenzyme Q10 of longer duration to assess benefits for diseases associated with ageing are needed. Abstract: Coenzyme Q10 (CoQ10 ) is an essential component of the mitochondrial electron transport chain. It is also an antioxidant in cellular membranes and lipoproteins. All cells produce CoQ10 by a specialized cytoplasmatic-mitochondrial pathway. CoQ10 deficiency can result from genetic failure or ageing. Some drugs including statins, widely used by inter alia elderly, may inhibit endogenous CoQ10 synthesis. There are also chronic diseases with lower levels of CoQ10 in tissues and organs. High doses of CoQ10 may increase both circulating and intracellular levels, but there are conflicting results regarding bioavailability. Here, we review the current knowledge of CoQ10 biosynthesis and primary and acquired CoQ10 deficiency, and results from clinical trials based on CoQ10 supplementation. There are indications that supplementation positively affects mitochondrial deficiency syndrome and some of the symptoms of ageing. Cardiovascular disease and inflammation appear to be alleviated by the antioxidant effect of CoQ10 . There is a need for further studies and well-designed clinical trials, with CoQ10 in a formulation of proven bioavailability, involving a greater number of participants undergoing longer treatments in order to assess the benefits of CoQ10 treatment in neurodegenerative disorders, as well as in metabolic syndrome and its complications.